RE: Are Cross-Sectional Imaging Modalities Enough for Sarcopenia Assessment? - Cankurtaran, Rasim Eren; Güneş, Yasin Celal; Dirican, Emre; Algın, Oktay; Cankurtaran, Damla; Yürekli, Öykü Tayfur (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Cankurtaran RE, Güneş YC, Dirican E, Algın O, Cankurtaran D, Tayfur Yürekli Ö. RE: Are cross-sectional imaging modalities enough for sarcopenia assessment? Turk J Gastroenterol. 2024;35(1):75.